“Just a Junior Journalist”: Field Theory and Editorial Photographers’ Gendered Experiences - Somerstein, Rachel (Journalism Practice, 2021)
Women outnumber men in graduate and undergraduate programs in photojournalism and work as photo editors at a number of high-profile publications. But in the field of professional editorial photography, they lag men in pay, legitimacy, and status. Using Bourdieu’s field theory, this paper explores how gender shapes the way women experience, compete in, and negotiate the field, specifically regarding assignments, salary, sexual harassment, and tactics for achieving access to stories. Findings suggest that women use their gender as a competitive advantage however they can, but that negative capital attached to femaleness and femininity persists. The findings are based on semi-structured interviews conducted between 2017 and 2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats.
Publisher: Routledge _eprint: https://doi.org/10.1080/17512786.2020.1755345
Keywords: Field theory; Myriam; gender; journalism; photojournalism; women and photography